Implementing a patient-oriented pole walking intervention in retirement homes: A non-randomized feasibility trial - Mohsen Keramati; Mahdi Rostami Haji Abadi; Saija Kontulainen (PLoS ONE, 2026)
Objectives To evaluate the feasibility and safety of implementing a patient-oriented pole walking (PW) intervention in retirement home settings and preliminary changes in outcome measures related to physical function and other fall- and fracture-related risk factors to inform a future randomized controlled trial (RCT). Methods This single-arm, non-randomized feasibility trial implemented a patient-oriented PW intervention across four retirement homes in Saskatoon, Saskatchewan, Canada. During Summer 2022, we assessed 24 residents for eligibility, of which 19 consented and 17 received the intervention. The intervention was offered as supervised group sessions (20–60 minutes) three times per week for 12 weeks. Each session consisted of posture and balance warm-up, PW, muscle strengthening, and stretching. The primary outcome measure was feasibility as assessed by consent, recruitment, retention, and adherence rates as well as by intervention acceptability, appropriateness, and feasibility scores. The secondary outcome measures included safety (evaluated by recorded adverse events) and preliminary 12-week changes in physical function and other fall- and fracture-related risk factors (examined with paired-samples t-tests or repeated measures analysis of covariance models). Results Fifteen participants (mean age 85.2 years; 93% female) completed the study. The consent, recruitment, retention, and mean adherence rates were 79%, 2.7 participants/site/month, 88%, and 90%, respectively. The mean participant- and instructor-reported scores for intervention acceptability, appropriateness, and feasibility were all > 4.0 (out of 5). There were no recorded intervention-related serious adverse events. Participants improved their functional balance/mobility (timed “up & go” test: −1.6 seconds; 95% CI: −2.7 to −0.4), lower-body strength (30-second chair stand test: 2.4 repetitions; 1.2 to 3.5), 36-item short-form survey physical functioning score (12.9; 3.7 to 22.2), and forearm muscle area (67.7 mm 2 ; 12.9 to 122.6) over 12 weeks. Conclusions It was feasible and safe to implement our patient-oriented PW intervention in retirement homes. Findings will inform our future RCT in these settings. Trial registration ClinicalTrials.gov NCT05388227 .